Identification and Assessment of Risks and Response Strategies in High-Rise Construction Projects - Shahin, Ahmed Magdy (2023)
A Master of Science thesis in Construction Management by Ahmed Magdy Shahin entitled, “Identification and Assessment of Risks and Response Strategies in High-Rise Construction Projects”, submitted in November 2023. Thesis advisor is Dr. Sameh El-Sayegh. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).